2019
DOI: 10.1016/j.dib.2019.103954
|View full text |Cite
|
Sign up to set email alerts
|

Operando X-ray absorption spectra and mass spectrometry data during hydrogenation of ethylene over palladium nanoparticles

Abstract: We report the series of Pd K -edge X-ray absorption spectra collected during hydrogenation of ethylene with variable ethylene/hydrogen ratio over carbon supported palladium nanoparticles. The data presented in this article includes normalized X-ray absorption spectra, k 2 -weighted oscillatory χ( k ) functions extracted from the extended X-ray absorption fine structure (EXAFS) and k 2 -weighted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…The observed decomposition of ethylene with the formation of carbide correlates with a number of previous reports [ 29 , 30 , 31 , 33 , 36 , 37 , 38 , 39 , 40 ]. The lattice expansion at 50 °C is, however, significantly reduced, in terms of both the kinetics and saturated values compared to the studies performed at higher temperatures [ 40 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The observed decomposition of ethylene with the formation of carbide correlates with a number of previous reports [ 29 , 30 , 31 , 33 , 36 , 37 , 38 , 39 , 40 ]. The lattice expansion at 50 °C is, however, significantly reduced, in terms of both the kinetics and saturated values compared to the studies performed at higher temperatures [ 40 ].…”
Section: Discussionsupporting
confidence: 90%
“…In the recent works of Bowker [ 29 , 30 , 31 ], it was highlighted that under industrially relevant pressures on real catalysts, the processes are different from that on ideal surfaces and high-vacuum conditions, which are typical for surface science studies. In addition, palladium can easily form carbide phase in the presence of hydrocarbons [ 29 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ], which affects its catalytic properties. For this reason, the application of bulk-sensitive structural methods in addition to surface-sensitive ones is important to understand the structural evolution of the metal.…”
Section: Introductionmentioning
confidence: 99%
“…In the same work it was also observed that in presence of hydrocarbons β-PdH is formed at much higher partial pressures of hydrogen comparing to Pd-H phase diagram obtained in pure hydrogen, 12 which indicates that an investigation of Pd-H/Pd-C phase diagram under different partial pressures of hydrogen and hydrocarbon molecules is required. In our recent works, formation of palladium carbides was observed in the presence of acetylene, 13-15 ethylene 14,16,17 and under reaction conditions, [16][17][18] which also highlighted irreversible changes in the catalyst structure in the time scales from minutes to hours. In the current work, we performed operando time-resolved study of supported palladium nanoparticles during ethylene hydrogenation by combined Pd K-edge extended X-ray absorption fine structure (EXAFS) spectroscopy, X-ray absorption near edge structure (XANES) spectroscopy, X-ray powder diffraction (XRPD) and mass spectrometry.…”
Section: Introductionmentioning
confidence: 72%
“…Palladium is well-known for its ability for dissociative adsorption and storage of hydrogen [1]. The hydrogen storage capacity and kinetics of hydrogen adsorption and desorption are strongly affected by the particle's size and shape [2][3][4][5][6][7][8], which is an important parameter for catalytic applications [8][9][10][11][12][13][14]. Bulk palladium materials exhibit a sharp phase transition from αto β-hydride, resulting in a characteristic plateau in the pressure composition isotherm [1].…”
Section: Introductionmentioning
confidence: 99%